Mortality, Osmoregulation, and Fat Depletion of Young-of-the-year of Some Species of Freshwater Fish in Winter Conditions - Toneys, Michael L (University of Wisconsin-Stevens Point, College of Natural Resources, 1977)
To determine if mortality during winter was higher for smaller young-of-the-year, freshwater fish, eight experiments were conducted in lakes and hatchery ponds in which fish were measured in late fall and early spring. Overwinter increase in mean length of bluegill, Lepomis macrochirus, in one lake and largemouth bass, Micropterus salmoides, in another was attributed to higher mortality of smaller fish. Size-specific mortality was not detected in two other bluegill populations, one largemouth bass, one green sunfish, Lepomis cyanellus, one fathead minnow, Pimephales promelas, and one white crappie, Pomoxis annularis, population. In laboratory experiments young-of-the-year green sunfish, largemouth bass, channel catfish, Ictalurus punctatus, brook trout, Salvelinus fontinalis, and yellow perch, Perea flavescens, were held for four months in simulated winter conditions (2-4°C, photoperiod of 9L:15D) in solutions of various osmotic strengths including 90% distilled water/10% tap water, tap water, 0.1, 0.2, 0.4, 0.5, 0.6, 0.85 and 1.0% NaCl. Mortalities occurred in 4 of the 6 experiments and often were greater in salt solutions, indicating that NaCl did not enhance survival. Larger fish tended to survive longer. Hematocrit was depressed below control levels for largemouth bass, brook trout, channel catfish, and yellow perch in all solutions at the end of experiments. All species generally were able to regulate plasma osmotic concentration in all solutions except the highest NaCl concentrations where plasma osmolality was often significantly higher than control levels at the end of experiments. Plasma Na+ and Cl^- concentrations usually were lower for experimental fish than control fish at the end of experiments, but they were frequently elevated in the highest salt concentrations. Fat content of survivors declined and water content increased for all species, but the losses and gains were not related to osmolality of solutions. Larger survivors tended to have more fat and less water. Low fat content probably was not a cause of mortality.